PD-1 induces autophagy via the PI3K/AKT/FoxO1 pathway to promote infectious bursal disease virus replication - Zhang, Qiuyu; Yue, Feng; Sun, Guopeng; Jiang, Liwei; Li, Peng; Zhu, Yanping; Liu, Zhike; Zhu, Yangzhao; Niu, Ruiyan; He, Hua; Sun, Zilong; Wang, Xuannian (Frontiers in Immunology, 2025)
IntroductionAutophagy is an important process in host cell responses to viral replication and spread, including those against infectious bursal disease virus (IBDV). Programmed death-1 (PD-1) is a known immunoinhibitory receptor, and its expression causes immune dysfunction in B lymphocytes, resulting in increased progression of immunosuppressive diseases. However, the role of PD-1 in autophagy during IBDV infection remains unclear.MethodsWe investigated the mechanism by which chicken PD-1 regulates autophagy during IBDV infection.ResultsIBDV infection enhanced PD-1 expression in chicken tissues and DT-40 cells. Subsequent interaction analyses revealed that PD-1 interacted only with the viral protein VP2 to enhance the IBDV replication in DT-40 cells. PD-1 overexpression significantly increased IBDV-induced autophagy, whereas silencing of PD-1 had the opposite effect in IBDV-infected DT-40 cells. Furthermore, PD-1 enhanced the activation of FoxO1 via the PI3K/AKT pathway. Finally, we demonstrated that autophagy is critical for role of PD-1 in regulating VP2 protein expression and IBDV titers.DiscussionThese findings present a novel mechanism wherein PD-1 induces autophagy by activating the PI3K/AKT/FoxO1 pathway to facilitate IBDV replication, providing a new avenue in developing universal vaccine adjuvants for IBDV infection control.